DEVELOPING NAHMA (NAHWU MATCHING) FOR BASIC NAHWU LEARNING GAME: A NEED ASSESSMENT STUDY - Mohamad Yusuf Ahmad Hasyim; Bernandus Wahyudi Joko Susilo; Jamat Jamil (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
In this epidemic era, teachers are expected to build a successful learning environment in conjunction with online learning. Basic nahwu learning is one of the lessons affected by the pandemic situation. Learning the Arabic language system is increasingly difficult to do online because the Arabic language system is very different from Indonesian, as the learners' mother language. The presentation of linguistic rules clearly cannot be done directly. Educators are responsible for innovating nahwu learning through the unity-based Nahma educational game